2014
DOI: 10.1186/s12870-014-0346-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stacking insecticidal cry and herbicide tolerance epsps transgenes on transgenic maize proteome

Abstract: BackgroundThe safe use of stacked transgenic crops in agriculture requires their environmental and health risk assessment, through which unintended adverse effects are examined prior to their release in the environment. Molecular profiling techniques can be considered useful tools to address emerging biosafety gaps. Here we report the first results of a proteomic profiling coupled to transgene transcript expression analysis of a stacked commercial maize hybrid containing insecticidal and herbicide tolerant tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 81 publications
2
48
0
1
Order By: Relevance
“…Therefore, additional studies could be performed in order to further investigate the correlation of transgene transcripts and levels of Bt toxin production, and even the bioefficacy of the transgenic proteins against the target organisms, and thus the biological meaning behind it. Taken together, our results are in agreement to that of our previous work that showed reduced transgene expression in stacked transgenes with the same GM event, but with different varieties [42]. We have observed a significant reduction of the expression of the cry2Ab2 transgenes in the stacked event.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, additional studies could be performed in order to further investigate the correlation of transgene transcripts and levels of Bt toxin production, and even the bioefficacy of the transgenic proteins against the target organisms, and thus the biological meaning behind it. Taken together, our results are in agreement to that of our previous work that showed reduced transgene expression in stacked transgenes with the same GM event, but with different varieties [42]. We have observed a significant reduction of the expression of the cry2Ab2 transgenes in the stacked event.…”
Section: Discussionsupporting
confidence: 93%
“…Agapito-Tenfen et al [42] also found reduced transgene expression in stacked transgenes with the same GM event, but with different varieties. The authors suggested that these reductions might be related to the high energetic demand of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, a further aspect of downstream risk assessment may be in the use of 'omics' analyses (transcriptomics, proteomics, metabolomics epigenomics, and miRNomics) to study dynamic changes of GM crops [95][96][97]. While these methodologies may see increasing future use and application toward genome-edited crops, they, at present, have limited regulatory applicability as the outcomes of 'omics' analyses are not well defined in the context of regulatory decisionmaking and the paradigm for comparative risk assessment [10].…”
Section: Downstream Risks Of Genome Editing For Crop Improvementmentioning
confidence: 99%